Rehabilitation of Educational Facilities Gardens In Agricultural Engineering Faculty In Damascus University (Damascus University Journal of agriculture sciences, 2026)
This research was conducted in Agricultural Engineering Faculty at Damascus University in 2023, as green areas are of great importance from the aesthetic, urban, environmental and planning aspects, and the gardens of educational  facilities have a special role in terms of the previous criteria, in addition to their educational purpose. Therefore, a field study was conducted for the gardens of the Faculty of Agricultural Engineering and the studied part has been determined, and the current status of the garden was raised in terms of its location and area, and the plant and structural coordination elements were identified with the aim of reconsidering its design scientifically. The results showed that the area allocated to green areas is very low and the areas allocated for creating gardens on college campuses amount to approximately 50% of the building area.    However, the establishment of these gardens was not based on the necessary  scientific and applied study and was created in an improvised manner due to  Lack of investment awareness in the field of gardens and estimating their economic return, lack of good preparations for an economic feasibility study, lack of available natural resources and not using them properly, lack of interest in gardens, and scarcity of specialists in the field of garden design and landscaping, so the allocated green spaces were not exploited appropriately, and based on that, we re- Studying the college gardens in terms of designing part of them again and rehabilitating the other part to correct the mistakes committed during their implementation. A detailed study was prepared, a design for the garden was drawn up, and the necessary executive plans were prepared in accordance with the scientific and applied methodology required. He sold it when designing the gardens of educational facilities, and the research concluded with several recommendations that call in their entirety for implementing Scientific standards in the distribution of green areas, which contributes to raising their efficiency. .
Keywords: Green Spaces; Design and Landscaping; Importance of Gardens; Educational Facilities Gardens